The “Nutritional Prevention” within italy’s National Prevention Plan 2020-25 - Alonzo, E.; Bonaccorsi, G.; Cairella, G.; Carreri, V.; Guberti, E.; Nucci, D.; Panunzio, M. F.; Valerio, E. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Italy’s National Prevention Plan 2020-25 is the first to address nutritional prevention, highlighting its importance in combating chronic diseases. This letter discusses the relationship between food safety, nutritional security, and the need for nutritional prevention in the plan. Chronic diseases, such as cardiovascular disease, cancer, and diabetes, are significant public health concerns in Italy, with poor nutrition being a critical risk factor. Incorporating nutritional prevention can promote healthy eating habits, food security and sustainability, reduce healthcare costs, and promote social cohesion and equality. Successful implementation will require cooperation among the government, the private sector, and the civil society to ensure healthier food choices and prevent chronic diseases in Italy.